2002
DOI: 10.1111/j.1744-7410.2002.tb00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and variability of trunk spines in the acanthocephalan Corynosoma cetaceum: the role of physical constraints on attachment

Abstract: Abstract. In this study, we investigated a functional trade‐off between trunk attachment and trunk‐spine development in the acanthocephalan Corynosoma cetaceum. The worms live attached to the stomach and upper intestine of their cetacean definitive hosts, using the proboscis and spiny foretrunk as the main holdfast; the spiny hindtrunk can also attach by bending ventrally. When the hindtrunk bends, ventral compression generates an anterior fold (AF) and a posterior fold (PF). A morphological analysis based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Specimens of C. cetaceum examined in the present paper agree in general terms with the characteristics that define the species; however, some differences in the number of proboscis hook rows (20-21 versus 18-9) and in the number of hooks per row (13-15 versus 12-13 or 14-16) were observed. The ventrally transverse folds delimiting a blunt lobe between the fore-and hind-trunks in the female, described by Aznar et al (1999bAznar et al ( , 2002b, were also observed in cystacanths in the present study.…”
Section: Locussupporting
confidence: 64%
“…Specimens of C. cetaceum examined in the present paper agree in general terms with the characteristics that define the species; however, some differences in the number of proboscis hook rows (20-21 versus 18-9) and in the number of hooks per row (13-15 versus 12-13 or 14-16) were observed. The ventrally transverse folds delimiting a blunt lobe between the fore-and hind-trunks in the female, described by Aznar et al (1999bAznar et al ( , 2002b, were also observed in cystacanths in the present study.…”
Section: Locussupporting
confidence: 64%
“…Being exposed to the strongest frictional drag, C. cetaceum exhibits not only the greatest development of Ds and VNR, but also the largest body spines of all Corynosoma species examined thus far [ 17 ]. As an interesting twist, females of C. cetaceum also have shorter bodies than males, contrary to most acanthocephalans [ 28 ], and are able to deeply fold the hindtrunk thanks to VNR contraction [ 29 ]. These features additionally reduce frictional drag, which helps females withstand the harsh microhabitat conditions in the stomach longer than males [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 i.e. the disk border, the interfold area, and the posterior hind-trunk (see Aznar et al 2002 a for details). For brevity, we will refer to the spines from these sites as Spines 1, 2 and 3, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Acanthocephalans, in particular, have developed a proboscis armed with hooks that anchor to the gut of their definitive host (Taraschewski, 2000). Many species also have trunk spines that engage on the gut surface, sometimes playing a significant role in attachment (Van Cleave, 1952;Aznar et al 1999aAznar et al , 2002a. It has been argued that investment in these primary holdfast structures is optimized for the species of host and the particular microhabitat where each species of acanthocephalan lives (Poulin, 2007).…”
Section: Introductionmentioning
confidence: 99%